Reconsidering Political and Popular Understandings of the Digital Divide - Selwyn, Neil (New Media & Society, 2004)
This article presents a theoretical examination of the digital divide, tracing its origins in the centre–Left social inclusion policy agenda of the 1980s and 1990s to its current status of political ‘hot topic’. It then moves on to outline four conceptual limitations to conventional dichotomous notions of the digital divide and individuals’ ‘access’ to information and communications technology (ICT): what is meant by ICT; what is meant by ‘access’; the relationship between ‘access to ICT’ and ‘use of ICT’; and a lack of consideration of the consequences of engagement with ICT. The article outlines a more sophisticated, hierarchical model of the digital divide based around these conceptual ‘stages’ while recognizing the mediating role of economic, cultural and social forms of capital in shaping individuals’ engagements with ICT. It concludes by developing a set of research themes and questions for future examination of inequalities in individuals’ use of ICT.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODA0MDQyNTE5